1994
DOI: 10.1097/00006842-199403000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Patient presentation, interview content, and the detection of depression by primary care physicians.

Abstract: This study was undertaken in order to better understand the detection of depression by primary care physicians. Specifically, we investigated the relationship between information gathered during the course of the medical interview and the subsequent diagnosis of depression. Forty-seven community-based primary care physicians, unaware of the mental health focus of this research, were videotaped in the office setting, as they interviewed two "typical" standardized patients who met DSM-III-R criteria for major de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 0 publications
2
30
0
5
Order By: Relevance
“…SC encounters are designed to simulate actual student-client interactions with a high degree of realism. The literature reports convincing evidence, and our own experience concurs that simulators can recreate medical signs (Barrows, 1971;Barrows & Abrahamson, 1964; and psychological or psychosocial information (Badger, deGruy, Hartman, Plant, Leeper, Anderson, et al, 1994;Badger, deGruy, Hartman, Plant, Leeper, Ficken, et al, 1994;Badger et al, 1995) with great fidelity. Therefore, SCs can be utilized by educators to ensure that all students experience the variety of clients and specific client problems fundamental to competent practice.…”
supporting
confidence: 67%
“…SC encounters are designed to simulate actual student-client interactions with a high degree of realism. The literature reports convincing evidence, and our own experience concurs that simulators can recreate medical signs (Barrows, 1971;Barrows & Abrahamson, 1964; and psychological or psychosocial information (Badger, deGruy, Hartman, Plant, Leeper, Anderson, et al, 1994;Badger, deGruy, Hartman, Plant, Leeper, Ficken, et al, 1994;Badger et al, 1995) with great fidelity. Therefore, SCs can be utilized by educators to ensure that all students experience the variety of clients and specific client problems fundamental to competent practice.…”
supporting
confidence: 67%
“…What might explain this finding? A recent study found that if a depressed patient presents with painful symptoms, inquiry about their DSM criteria symptoms is generally low and information acquired is rarely sufficient to make a formal diagnosis of depression [27]. Considering PCPs' evaluations of the patients' presenting symptoms, pain might lead to a hypothesis of "organic" dysfunction, with a greater amount of the medical visit time dedicated to technical tasks or diagnostic procedures [28].…”
Section: Discussionmentioning
confidence: 99%
“…Half of all serious cases of depression go unrecognised in primary care, especially those where patients present with physical symptoms. 23 24 In addition, patients often focus on physical symptoms rather than the psychosocial consequences of their illness. 25 26…”
Section: Discussionmentioning
confidence: 99%